2019
DOI: 10.3329/ralf.v6i1.41392
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of hydroponic wheat sprouted fodder on growth performance of turkey

Abstract: The study was conducted at Faculty of Veterinary and Animal Science, Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur, Bangladesh to determine the nutritional composition and economic value of hydroponic wheat sprouted fodder (HWSF) replaced by commercial concentrate feed (CCF) and it’s effect on growth performance of turkey. A total of 75 poults were selected and randomly assigned into five groups (T1, T2, T3, T4 and T5), each group with 3 replications having 15 birds in each. T1 consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
3
8
0
Order By: Relevance
“…Similarly, other study also reported no significant difference between various dietary protein levels on serum biochemistry profile. The results are also in agreement with the results obtained was slightly higher values of total protein and serum calcium on turkey fed on alfalfa diet [13,14,15,16].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, other study also reported no significant difference between various dietary protein levels on serum biochemistry profile. The results are also in agreement with the results obtained was slightly higher values of total protein and serum calcium on turkey fed on alfalfa diet [13,14,15,16].…”
Section: Discussionsupporting
confidence: 92%
“…On the third day of germination, chloroplast formation and photosynthesis start, but in this short time (seven days), the dry matter accumulation by photosynthesis cannot meet the loss [54]. Ali et al [55] studied the dry matter content of germinated wheat and maize. Loss of dry matter is inevitable, although there is no scientific literature on how to reduce the loss.…”
Section: Discussionmentioning
confidence: 99%
“…Sprouting, a methodology which improves the nutrient content of grains, has been applied in various studies on many plants. The addition of hydroponic wheat sprouts at 150 g/kg of feed notably enhanced the overall growth parameters of turkeys ( Ali et al, 2019 ). In addition to growth performance, sprouted seeds have been shown to positively impact animal health.…”
Section: Introductionmentioning
confidence: 99%